Timing of pharmacologic venous thromboembolism prophylaxis initiation for trauma patients with nonoperatively managed blunt abdominal solid organ injury: a systematic review and meta-analysis - Lamb, Tyler; Lenet, Tori; Zahrai, Amin; Shaw, Joseph R.; McLarty, Ryan; Shorr, Risa; Le Gal, Grégoire; Glen, Peter (Université d'Ottawa | University of Ottawa, 2022)
Abstract Background Blunt abdominal solid organ injury is common and is often managed nonoperatively. Clinicians must balance risk of both hemorrhage and thrombosis. The optimal timing of pharmacologic venous thromboembolism prophylaxis (VTEp) initiation in this population is unclear. The objective was to evaluate early (< 48 h) compared to late initiation of VTEp in adult trauma patients with blunt abdominal solid organ injury managed nonoperatively. Methods Embase, MEDLINE, and the Cochrane Central Register of Controlled Trials were searched from inception to March 2021. Studies comparing timeframes of VTEp initiation were considered. The primary outcome was failure of nonoperative management (NOM) after VTEp initiation. Secondary outcomes included risk of transfusion, other bleeding complications, risk of deep vein thrombosis (DVT) and pulmonary embolism, and mortality. Results Ten cohort studies met inclusion criteria, with a total of 4642 patients. Meta-analysis revealed a statistically significant increase in the risk of failure of NOM among patients receiving early VTEp (OR 1.76, 95% CI 1.01–3.05, p = 0.05). There was no significant difference in risk of transfusion. Odds of DVT were significantly lower in the early group (OR 0.36, 95% CI 0.22–0.59, p < 0.0001). There was no difference in mortality (OR 1.50, 95% CI 0.82–2.75, p = 0.19). All studies were at serious risk of bias due to confounding. Conclusions Initiation of VTEp earlier than 48 h following hospitalization is associated with an increased risk of failure of NOM but a decreased risk of DVT. Absolute failure rates of NOM are low. Initiation of VTEp at 48 h may balance the risks of bleeding and VTE.